Study on model of greenhouse gas N2O emission flux of rice field in cold region in growing season in water-saving irrigation mode. (2018) - Lihong, Yu; Mengxue, Wang
Under the condition of field experiment, three water management modes of control irrigation, intermittent irrigation and flood irrigation were set, a static black-box-gas chromatographic method was adopted for field in-situ observation on N2 O emission flux of cold region rice field in the growing season, and optimal single-factor model and interaction model of N2 O emission flux of rice in different water management modes in the growing season were established by using test data of 2014. The interaction model can effectively describe the response features of rice field N2 O emission flux to soil nitrate nitrogen and temperature coordinated variation better than any single-factor model. The models of the study can be used for estimating N2 O emission flux of rice field in the growing season in cold region of China.